Perception of Perusahaan Otomobil Kedua Sdn Bhd (PERODUA) on customer loyalty towards their products / Radziah Md Ridzuan - Md Ridzuan, Radziah (2009)
This case studies the way in “Perception of Perusahaan Otomobil Kedua Sdn Bhd (PERODUA) On Customer Loyalty towards Their Product”. Loyalty is the crucial elements for every organization. The cost of selling to new customers is much higher than the cost of selling the existing customers. Therefore, it is important for the company to foster customer loyalty. Furthermore, element contribute in customer loyalty is trust, commitment, communication and conflict handling have been identified in order to investigate whether or not these element have significant relationship with customer loyalty. The objectives of this case study are to determine the level of customer loyalty and its elements towards Perodua Manufacturing Sdn. Bhd towards their product. This is important to Perodua Manufacturing Sdn. Bhd (PMSB) as it will help them determine the main problems faced by their company in other to retain customer loyalty and the organization profitability will increase day to day. Furthermore, organization performance will success effectively and efficiency. An organization will increase their profitability as long as customer loyalty towards with their brands. In order to complete this case study, interview is way to get the information needs is relevant, accurate, reliable, valid, current and actionable information. The respondent for this interview is for those which had experience in using PERODUA products (cars) as their daily transportation. For collection data, will use both technique which primary data and secondary data.